Łączka, amazońska dżungla i Chicago. Patrycja Rojek* i Andrzej Szpulak* rozmawiają z dokumentalistą, niezależnym producentem i dyrektorem Festiwalu Niepokorni Niezłomni Wyklęci – Arkadiuszem Gołębiewskim. - Rojek, Patrycja; Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
In this interview, Arkadiusz Gołębiewski discusses his film work, and activity as producer and head of the NNW Festival in Gdynia. In addition, the director also talks about his work relating to the post-war Polish (military anti-communist underground) and other custom projects. He also comments on a situation of historical documentary in Poland.